A study to assess body mass index and pattern of physical activity among the government employees working at different organizations of Gwalior city - Mahore, Rakesh Kumar; Tiwari, Ranjana; Bansal, Manoj; Gupta, Rajesh; Sharma, Vikash; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2018)
Background: The obesity can be defined simply as the disease in which excess body fat has accumulated to such an extent that health may be adversely affected. Physical activity is a key determinant of energy expenditure, and thus is fundamental to energy balance and weight control. Aims and objectives was to assess the BMI and physical activity among government employees working in different organizations of Gwalior city. Methods: The present study was a cross sectional study. Five different government organizations were selected and from each organization 60 participants were selected randomly. A pre-designed, pre-tested, semi-structured interview based questionnaire was used for data collection from different participants. WHO BMI classification was used to classify participants. Results: In the present study 44% of the study participants were overweight/ pre-obese while 8.33% and 1.33% were in Obese Class I and Obese Class II respectively. 40.67% were doing physical exercise. The most common type of physical exercise was walking or jogging 72.13%. Conclusions: It was concluded that despite the known fact that obesity could have negative impact on the work capacity and physical fitness, only 40.67% were doing some physical exercise. Employees should be motivated to do daily exercise for the duration of at least 30 minutes.